2017
DOI: 10.1080/02699052.2016.1231343
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary investigation of Brain Network Activation (BNA) and its clinical utility in sport-related concussion

Abstract: Background: The clinical diagnosis and management of patients with sport-related concussion is largely dependent on subjectively reported symptoms, clinical examinations, cognitive, balance, vestibular and oculomotor testing. Consequently, there is an unmet need for objective assessment tools that can identify the injury from a physiological perspective and add an important layer of information to the clinician’s decision-making process. Objective: The goal of the study was to evaluate the clinical utility of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…Specifically, mTBI participants frequently demonstrate evoked potentials that are delayed and weaker compared to peers (Broglio, Pontifex, O’Connor, & Hillman, 2009; Duncan, Kosmidis, & Mirsky, 2003; Larson, Farrer, & Clayson, 2011). Yet only a few reports have examined group differences in response-locked functional connectivity, for example, during set-shifting (Pang, Dunkley, Doesburg, da Costa, & Taylor, 2016), target detection (Reches et al, 2017), working memory (Bailey et al, 2017; Kumar, Rao, Chandramouli, & Pillai, 2009), and learning tasks (Tsirka et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, mTBI participants frequently demonstrate evoked potentials that are delayed and weaker compared to peers (Broglio, Pontifex, O’Connor, & Hillman, 2009; Duncan, Kosmidis, & Mirsky, 2003; Larson, Farrer, & Clayson, 2011). Yet only a few reports have examined group differences in response-locked functional connectivity, for example, during set-shifting (Pang, Dunkley, Doesburg, da Costa, & Taylor, 2016), target detection (Reches et al, 2017), working memory (Bailey et al, 2017; Kumar, Rao, Chandramouli, & Pillai, 2009), and learning tasks (Tsirka et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…ERP's are typically labeled by their polarity (P for positive or N for negative) and their time of occurrence after the stimulus in milliseconds (e.g., P300). Numerous studies have reported ERP-related differences between mTBI and control groups, even as some of these found no differences using neuropsychological measures [19][20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…According to Haneef et al [21], the acute, subacute, and chronic mTBI stages can be mapped out using qEEG measurements, suggesting that this technique could be used for diagnosis and monitoring recovery. Although analysis for unique EEG components in a mTBI is showing a lot of potential, it still requires the use of a large number of electrodes [22], making rapid measurements problematic.…”
Section: Introductionmentioning
confidence: 99%